Personal traits according to the model of the list of the big five factors and self-efficacy and their relationship to the motivation of sports achievement for young handball players, a survey research - Mahmood Ahmed, Falah (International Journal of Psychosocial Rehabilitation, 2020)
The follower of what is happening in the world of achievements will find there is a comprehensive scientific development for all scientific fields and in their various forms and types, and the sports field takes its share and right every day from this wide development that reaching a new level and achieving achievement in international forums is important for all sports teams in all Games, and that this progress is not the result of chance but is the result of research, investigation, and scientific and technical efforts exerted by experts and coaches in the field of sports and in regular and deliberate ways to reach the best to serve the players. The essence of the human being is closely related to the responses of other athletes, so most scholars agreed that personality traits are among the most complex phenomena that psychology is subjected to studying because they are a multidimensional and multifaceted psychological phenomenon. It is considered the decisive factor in achieving maximum performance, especially in the sports field, as it means the extent to which the handball player believes that he can successfully implement what is required of him. All the requirements of sports performance in order to achieve a certain result required of him, and the achievement motivation is no less important than the concepts of personality and self-efficacy, as it is a multi-dimensional composition, and that achievement situations are situations in which the greatest attention for the player is on his personal competence to meet the requirements of the situation, and that the goals or attitudes are among the most important determinants of achievement behavior based on the interpretation of the success or failure of the achievement behavior in light of the extent to which these goals or directions have been achieved.